Chloroplast Genomes of Genus Tilia: Comparative Genomics and Molecular Evolution - Yan, Linjun; Wang, Huanli; Huang, Xi; Li, Yingchao; Yue, Yuanhao; Wang, Zhongwei; Tang, Shijie (Frontiers in Genetics, 2022)
Tilia is a complex genus in the family Malvaceae that has high ecological and economical values. Owing to the lack of sufficient distinguishable morphological and molecular characteristics, interspecific relationships in this genus are not clear. Chloroplast (cp) genomes are small and most angiosperms usually undergo matrilineal inheritance; consequently, they can be used in molecular systematics and phylogenetic analyses. Here, we sequenced and assembled Tilia cp genomes from T. endochrysea, T. tomentosa, T. miqueliana, T. americana and T. cordata, and compared them with those of seven previously reported Tilia species. Similar gene contents, gene orders and GC contents existed among the 12 cp genome sequences, which ranged from 162,564 to 162,855 bp and encoded 113 unique genes. Using a comparative genomic analysis, abundant simple sequence repeats (119 to 127) and dispersed repeats (97 to 135) were detected in Tilia cp genomes. In total, 11 hypervariable regions were identified that could be suitable for species identification and phylogenetic studies. A phylogenetic analysis of Malvaceae based on 5 hypervariable genes (matK+ndhF+rpoB+rpoC2+ycf1) revealed that all eight subfamilies were monophyletic groups. Revealed that all eight subfamilies were monophyletic groups. Additionally, the genus Tilia was divided into three groups on the basis of all 521 molecular variation loci. The current study provides valuable insights into the genomic evolution of the genus Tilia.